Upaya Meningkatkan Hasil Belajar Matematika Materi Segi Banyak Beraturan Menggunakan Metode Diskusi pada Siswa Kelas IV SDN 17 BPR Ranau Tengah - Seripaton Aini; Dita Mulyana Ramadhani; Irmawati M; Uhwah Hasanah; St Harpiani (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This research aims to improve student learning outcomes in Mathematics lessons by using the Regular Polygon learning material discussion method. The subjects of this research were fourth grade students at SDN BPR Ranau Tengah. This research is Classroom Action Research which was carried out in 2 cycles. The data collection technique used is observation. The instrument used is a direct observation sheet. From the research results, it is known that using the discussion method can improve student learning outcomes regarding regular polygons in class IV students. Students' understanding in mathematics lessons about regular polygons before being given action was 30% and was in the poor category. After using the discussion method in cycle I it increased to 50% and was in the sufficient category. In cycle II, students' abilities increased again to 70% and were in the good category. Apart from that, students can also improve their understanding of regular polygon material and gain knowledge, especially for groups with medium and low abilities. By forming the right study group you can also improve group performance, so that it will benefit all group members. From the results of this research it can be concluded that the discussion method can improve student learning outcomes.